Advancements in chondrocyte 3-dimensional embedded culture: Implications for tissue engineering and regenerative medicine - Yu-Ying Chu; Atsuhiko Hikita; Yukiyo Asawa; Kazuto Hoshi (Biomedical Journal)
Cartilage repair necessitates regenerative medicine because of the unreliable healing mechanism of cartilage. To yield a sufficient number of cells for transplantation, chondrocytes must be expanded in culture. However, in 2D culture, chondrocytes tend to lose their distinctive phenotypes and functionalities after serial passage, thereby limiting their efficacy for tissue engineering purposes.The mechanism of dedifferentiation in 2D culture can be attributed to various factors, including abnormal nuclear strength, stress-induced mitochondrial impairment, chromatin remodeling, ERK-1/2 and the p38/mitogen-activated protein kinase (MAPK) signaling pathway. These mechanisms collectively contribute to the loss of chondrocyte phenotype and reduced production of cartilage-specific extracellular matrix (ECM) components.Chondrocyte 3D culture methods have emerged as promising solutions to prevent dedifferentiation. Techniques, such as scaffold-based culture and scaffold-free approaches, provide chondrocytes with a more physiologically relevant environment, promoting their differentiation and matrix synthesis. These methods have been used in cartilage tissue engineering to create engineered cartilage constructs for transplantation and joint repair.However, chondrocyte 3D culture still has limitations, such as low viability and proliferation rate, and also difficulties in passage under 3D condition. These indicate challenges of obtaining a sufficient number of chondrocytes for large-scale tissue production. To address these issues, ongoing studies of many research groups have been focusing on refining culture conditions, optimizing scaffold materials, and exploring novel cell sources such as stem cells to enhance the quality and quantity of engineered cartilage tissues.Although obstacles remain, continuous endeavors to enhance culture techniques and overcome limitations offer a promising outlook for the advancement of more efficient strategies for cartilage regeneration.